Histopathological Study of Sinonasal and Nasopharyngeal Lesions in Sumber Waras Hospital Jakarta from 2017-2023 - Yunita Dewi; Sony Sugiharto (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2024)
Background: Various non-neoplastic and neoplastic lesions arise from the sinonasal tract and nasopharynx. Polyps are the most frequently reported sinonasal lesions, with a prevalence of 2 %. Nasopharyngeal carcinoma is a common malignancy in Indonesia, with 19.943 new cases. Histopathological examination is the gold standard for diagnosis because management and prognosis vary among different lesions. Objective: The aim is to determine the incidence of various non-neoplastic and neoplastic lesions and to study the histopathological features with regard to age and gender. Methods: This study was a descriptive observational study with a cross-sectional design. The sample was retrieved from the histopathological records in Sumber Waras Hospital Jakarta from February 2017 to December 2023. The inclusion criteria were all patients with sinonasal or nasopharyngeal lesions that have been biopsied and then done histopathological examination at Sumber Waras Hospital Jakarta. The exclusion criteria were incomplete data and patients with histopathological diagnoses of necrotic tissue and inflammation. The sample consisted of 73 patients with a total of 76 cases, as 3 patients had multiple diagnoses. The data collected were later analyzed with SPSS software. Results: Among 73 patients, 54 were males and 19 were females. A maximum number of cases were diagnosed in the age group of 51-60. Among 43 sinonasal lesions, 25 (58,2%) were non-neoplastic and 18 (42%) were neoplastic lesions. Inflammatory polyps (42%) were the most common among the sinonasal lesions. Of 33 nasopharyngeal lesions, there were 2 (6,1%) non-neoplastic and 31 (93,9%) neoplastic lesions. The majority of these were of nasopharyngeal carcinoma (84,8%). Conclusion: Histopathological examination is essential for diagnosing and classifying sinonasal and nasopharyngeal lesions.